Unsustainable. - Fingleton, Eamonn (American Prospect, 2000)
Behind a record period of U.S. economic expansion, with low inflation, high employment, and growing GDP, lies the specter of a trade deficit that keeps growing. The trade deficit in April 2000 of $30.4 billion was just fractionally below the record March deficit of $30.6 billion, and the narrowing of the gap in April appears to have been no more than a temporary aberration. These record deficits have hardly caused a ripple of concern among the public, however. In the past, the conventional economic understanding was that a country running a large deficit would be unable to pay for all the products it imported. The triumphalist economic view at present is that trade deficits no longer matter. The reality is that the negative implications of growing U.S. trade deficits are numerous; and it may not be too much of an overstatement to say that unless the government can quickly reverse the trade trend, the country's time as the world's leading economy might be over. The declining competitiveness of the U.S. in comparison with Europe and Japan, its dependence on other countries, and why trade deficits matter are discussed.